Chemiluminescence biosensor for hydrogen peroxide determination by immobilizing horseradish peroxidase onto PVA-co-PE nanofiber membrane. (June 2017) - Luo, Mengying; Wang, Wenwen; Zhao, Qinghua; Li, Mufang; Chen, Yuanli; Lu, Zhentan; Liu, Ke; Wang, Dong
Graphical abstract: Highlights: HRP was immobilized on PVA-co-PE nanofibers, creating a high catalytic activity membrane. The HRP-immobilized membrane exhibited enhanced activity, high sensitivity and good reusability. The HRP-immobilized membrane was demonstrated with potential application in food safety detection. Abstract: Poly(ethylene- co -polyvinyl alcohol) (PVA- co -PE) nanofiber membrane with abundant active hydroxyl groups on the surface was modified through a solid-phase synthesis process. The PVA- co -PE nanofibers with different average diameters ranging from 200 to 500 nm were modified by cyanuric chloride and 1, 3-propanediamine. The aminated PVA- co -PE nanofiber membrane was subsequently biotinylated and then horseradish peroxidase (HRP) was successfully immobilized onto it. The morphologies, hydrophilicity and chemical structures of membranes surface were investigated by SEM, water contact angle, FTIR and XPS. The HRP-immobilized PVA- co -PE nanofiber membrane revealed high activity, efficiency, sensitivity and reusability when it was used to catalyze the luminol-H2 O2 reaction. The results demonstrated that the HRP-immobilized PVA- co -PE nanofiber membrane could be a promising candidate as solid support materials for catalysis of Luminol-H2 O2 . The relative light unit (RLU) could run up to 5 × 10 5 when the H2 O2 concentration was low to 1 × 10 −15  mol/L. The HRP-immobilized PVA- co -PE nanofiber membrane was the potential chemiluminescence biosensor which could be applied in biological, medical and food fields.